Identifying and ranking critical success factors of Nine Challenges in Malaysian Vision 2020 - Islam, Rafikul (2008)

(untitled)
By the year 2020, Malaysia aspires to become a fully developed nation. In order to realize this vision, Malaysia needs to address nine strategic challenges identified by the former Malaysian Prime Minister Tun Dr. Mahathir bin Mohamad. The challenges are: (1) Establishing a united Malaysian nation, (2) Creating a psychologically liberated, secure, and developed Malaysian society, (3) Developing a mature democratic society, (4) Forming a community that has high morale, ethics, and religious strength, (5) Establishing a mature, liberal and tolerant society, (6) Establishing a scientific and progressive society, (7) Establishing a fully caring society, (8) Ensuring an economically just society, and (9) Establishing a prosperous society. The present paper intends to identify and rank the critical success factors of these nine challenges by applying Analytic Hierarchy Process. The findings are expected to provide valuable guidelines to the Malaysian government in course of developing effective action plans to achieve Vision 2020.